Design and Implementation of Children Tracking System using IoT - Samaan, Sama (Al-Nahrain Journal for Engineering Sciences, 2019)
In the past few years, all over the world, crime against children has been on the rise, and parents always worry about their children whenever they are outside. For this reason, tracking and monitoring children have become a considerable necessity. This paper presents an outdoor IoT tracking system which consists of a child module and a parent module. The child module monitors the child location in real time and sends the information to a database in the cloud which forwards it to the parent module (represented as a mobile application). This information is shown in the application as a location on Google maps. The mobile application is designed for this purpose in addition to a number of extra functions. A Raspberry Pi Zero Wireless is used with a GSM/GPS module on shield to provide mobile communication, internet and to determine location. Implementation results for the suggested system are provided which shows that when the child leaves a pre-set safe area, a warring message pops up on the parent’s mobile and a path from the current parent location to the child location is shown on a map.